Interactive web based learning systems software requirements engineering course / Wong Ing Hee - Wong, Ing Hee (2005)
Interactive Web Based Learning System for Requirement Engineering Course is a web based course information system developed to facilitate the teaching and learning process of Software Requirement engineering Course at Faculty Computer Science & Information Technology, University of Malaya. This Web Based Learning System is designed to create an information rich environment of education resources, which can be obtained at any time from any place to save the users' time. This system is divided into two main modules, which are lecturer's module and student's module. The Web Based Learning system serves as an alternative method for a lecturer to run a course. It allows lecturer to perform the course and lecture notes maintenance, tutorial maintenance, assignment maintenance as well as appointment. In other hand, the system enables the students who take Software Requirement Engineering Course to submit their assignments and get the teaching materials faster. It is more secure and time-saving conducting these events throughout the system. The Users can use this system as long as the connection to the web server and database server is established. The users have to logon to the system to center either lecturer's or student's section. Therefore, this system gives better quality education, services and facilities to the both students lecturer.